L’usage de la télédétection pour l’évaluation économique des écosystèmes marins : application à l’aire marine protégée de Tristão en Guinée - Vincent Turmine; Thomas Binet; Pierre Failler (VertigO)
This article exposes methods and results of a remote sensing exercise based on combined classifications and spatial analysis. This work was carried out as part of the EVA programme which looked at estimating the economic and social value of marine ecosystems within West African Marine Protected Areas (MPA). The remote sensing methods utilised in this study are innovative in that they stem from non supervised combined classifications and principal component analysis. These techniques offer a reliable method for the calculation of ecosystem surfaces, as well as estimation of their health status, both elements that are compulsory to the economic valuation exercises. From an application perspective, this modelling process is particularly relevant to regions of data-poor marine ecosystem mapping where biodiversity conservation is developed or large-scale areas where access is made difficult and costly in time and financial resources. Further, these results are likely to influence the identification of priority areas for conservation measures as part of the MPA management plan.